Hubungan Antara Motivasi Belajar dan Kepatuhan Mengumpulkan PR pada Anak Kelas IV Dan V di SD Negeri 104237 Dalu Sepuluh B - Abdillah Husein; Muhammad Halqi; Nurhalimah Nurhalimah; Putri Zahwa (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is driven by the low level of student motivation in completing homework at SD Negeri 104237 Dalu Sepuluh B. Motivation serves as a key factor that encourages students to be enthusiastic about learning. This study applies a descriptive qualitative method, which aims to present events or facts as they occur in the field, where the researcher acts as the main instrument in the process. Data were collected through observation, interviews, and documentation. The findings reveal that students’ motivation to do homework at SD Negeri 104237 Dalu Sepuluh B is relatively low. This is reflected in the first indicator, namely the willingness to make efforts despite repeated failures, where students appear indifferent toward homework assignments. The second indicator concerns the habit of completing homework early, which shows that students rarely work on assignments and only do so when they have spare time. The third indicator is activeness during lessons, where students are less engaged in responding to teachers, resulting in minimal interaction between students and teachers in the classroom, and their attention to lessons is limited. The fourth indicator relates to punctuality in submitting homework, as students are less disciplined in turning in assignments, often prioritizing tasks from the Islamic boarding school. The main inhibiting factor of students’ motivation in doing homework is the busy schedule of boarding school activities, which makes it difficult for students to manage their time to complete assignments.